PERBANDINGAN INFORMASI CITRA ANTARA SEQUENCES T2 FAST FIELD ECHO DAN SUSCEPTIBILITY WEIGHTED IMAGING PADA PEMERIKSAAN MRI BRAIN IRISAN AXIAL DENGAN KASUS MICROBLEEDS - Afandi; Luthfi Rusyadi; Fatimah; Jeffry Ardiyanto (JRI (Jurnal Radiografer Indonesia), 2018)
Background : The Gradient echo sequence is a sequence using RF excitation pulse varied and with flip NMV through various angle (Instead of 900). It’s sensitive in detecting the present of hemorrhages that have susceptibility and blooming effect to hemorrhages. T2 fast field echo (T2 FFE) and susceptibility weighted imaging (SWI) are part of the gradient echo pulse sequences, in which T2 FFE sequences is conventional non- steady state imaging 2D milti-slice and SWI is 3D velocity compensated sequence gradient echo. On both the sequence is very good for asses the hemorrhages particularly microbleeds. This study aims to determine differences in image information and determine the most optimal image information between T2 FFE and SWI sequences in brain MRI axial slices with microbleeds cases. Methods : Type of research is quantitative experimental approach. The data was taken from October to November 2016 at Radiology Installation of Siloam Hospital Lippo Village. The study populations was all examinations brain MRI with the microbleeds cases, 5 samples with inclusion criteria described. Scanning by using T2 FFE and SWI sequences, then evaluation by respondents furthermore the data was processed using kappa test, and analyzing the date using wilcoxon test, and then to get an assesment of the most optimal images seen from the mean rank wilcoxon test. Results : The result was p-value 0,025 (p<0,05) means that Ho refused and Ha accepted, so that statistically showed significant differences at images information between T2 FFE and SWI sequences in examinations brain MRI axial slices with microbleeds case, with mean rank on SWI sequence is 3, and mean rank on T2 FFE is 0, so it’s can be concluded that SWI sequence produces a better images information on the examination brain MRI axial slices with microbleeds cases than T2 FFE sequence. Conclusion : there is a difference of images information between T2 FFE and SWI sequences in Brain MRI axial slices with microbleeds cases, and SWI sequences produces a better images information on the Brain MRI axial slices with microbleeds cases.